The influence of thermohumid conditions on compression-after-impact properties of fibre-reinforced laminate materials - Roslan A. Aziz (2000)
Advance composite materials based mainly on epoxy resins are being used in increasing amounts in aerospace components due to their high strength:weight ratio. Such components have to survive in a range of temperature and humid environments in different parts of the world. The current generation of epoxy resins used in high performance fibre reinforced laminates absorb moisture from the atmosphere. Moisture absorption by the epoxy resins leads to a reduction in glass transition temperature and to a softening of the resin with a loss of resin stiffness and strength. In certain applications the components have to survive low impacts from dropped tools and rough handling during maintenance. Low energy impacts of this nature are considered potentially dangerous mainly because the damage might be left undetected. Even where no visible impact damage is observed at the surface, matrix cracking and interlaminar failure can occur, and the load carrying properties of the composite components is considerably reduced. A compression after impact (CAI) test is widely used in industry as the major screening parameters for materials selection. The aim of the work reported in this thesis was to determine the influence of thermohumid conditions on CAI properties and to assess the degradation behaviour of composite laminates under these thermohumid conditions. [Continues.]